Identity of the Suspect in Cyber Sabotage (Law, State and Telecommunications Review, 2023)
[Purpose] The purpose of the study is to identify means and measures to counteract and prevent cyber sabotage.[Methodology] The research is based on a systematic approach and logical tools (description, analysis, synthesis, induction, deduction, etc.). Special scientific, general scientific, and philosophical methods are applied.[Findings] The study analyses the possible motives of the suspect in cyber sabotage and unifies classification approaches. Attention is focused on information support for the interrogation of a suspect in cyber sabotage by an investigator to learn the identity of the suspect. Certain features of the sources of obtaining information about a person suspected of committing cyber sabotage are noted. The general characteristics and features of the identity of a cyber sabotage suspect cannot be considered outside the context of other socially dangerous attacks in cyberspace. The development of mechanisms for countering cybercrime in Ukraine continues.[Value] The practical significance of the study is determined in the list of measures and means proposed by the authors to reduce the risk of cyber sabotages and eliminate their harmful consequences.